Using health information for community activism: A case study of the movement for change and social justice in South Africa. - Myrna van Pinxteren; Christopher J Colvin; Sara Cooper (Public Library of Science (PLoS), 2022)
The access to, use, and exchange of health information is crucial when strengthening public health services and improving access to care. However, many health system stakeholders, including community groups are perpetually excluded from accessing and using health information. This is problematic as community groups, themselves end-users of care, are well-positioned to keep the health system accountable, provide feedback on the quality of services, and identify emerging health concerns. Using qualitative, ethnographic methods, this paper investigates different strategies used by the Movement for Change and Social Justice (MCSJ)-a local health activism group-to collect, use and distribute health information to improve health care in Gugulethu, a low-income neighbourhood in Cape Town, South Africa. Through participant observation, shadowing, informal conversations and semi-structured interviews that were analysed using iterative thematic analysis, findings revealed that MCSJ effectively collected, used and exchanged health information to develop short-term health campaigns. To get access to the needed health information, they used innovative strategies, including cultivating allies in the health system, finding safe spaces, and using community brokers to effectively mobilise community members to keep the health system accountable. MCSJ's strategies highlight that stakeholders' engagement with health information is not only a technical exercise, but a complex social process that requires constant negotiation and relationship building. Therefore, to make meaningful improvements to health services and create adaptive and responsive health systems, we need to include community groups as active stakeholders in the health system, provide relevant, up-to-date and locally relevant health information, and facilitate opportunities to socially engage with health information and those who produce it.